Health-Related Concerns of People who Receive Psychological Support for Inflammatory Bowel Disease - Robert G Maunder; Elizabeth C de Rooy; Brenda B Toner; Gordon R Greenberg; A Hilary Steinhart; Robin S McLeod; Zane Cohen (Canadian Journal of Gastroenterology)
BACKGROUND: People with inflammatory bowel disease (IBD) cope with a number of disease-specific concerns, which may result in referrals for supportive counselling.